Evidence of gill migration in monogenean polyopisthocotylean Microcotyle sebastis larvae infesting Korean rockfish (Sebastes schlegelii) - Won-Sik Woo; Gyoungsik Kang; Kyung-Ho Kim; Ha-Jeong Son; Min-Young Sohn; Min-Soo Joo; Chan-Il Park (Aquaculture Reports, 2024)
In contrast to the well-documented motility of monopisthocotyleans within the monogenean group, the mobility of polyopisthocotyleans, such as Microcotyle sebastis, has largely been undocumented with empirical evidence. This study aimed to investigate the locomotion of the polyopisthocotylean parasite of M. sebastis, which infests Korean rockfish (Sebastes schlegelii), thereby providing tangible evidence of early behavior in polyopisthocotyleans. The oncomiracidium of M. sebastis demonstrated movement facilitated by the hamulus and bilateral cilia, aiding in directional changes and propulsion. In the gill filaments of M. sebastis larvae utilized both the hamulus and their entire body for initial movements, effectively navigating between gill filaments. The hamulus played a crucial role in the locomotion of the early larval stages before the development of three clamp pairs, after which it began to degenerate. This study presents concrete evidence of early mobility in polyopisthocotyleans like M. sebastis, offering insights that could inform aquaculture management strategies, particularly in the mitigation of parasite-induced damages.